China's political and economic activities in Africa: development and environmental concerns - Shuriye, Abdi Omar (Islamic Centre for Research and Development, 2010)
In recent years, China's rapid economic growth and increasing political clout have significantly accelerated the country's involvement in African. Analysts suspect that its activities are multi-layered with unambiguous agenda to secure joint ventures for long-term economic expansion and for advancing its geopolitical ambitions. Nonetheless, these are not taking place without environmental and ecological concerns. China National Petroleum Corporation is exploring oil basins in many countries in Africa including Kenya and Ethiopia after its successful experience in S. Africa, Nigeria, Algeria, Morocco, Angola, Zimbabwe, Rep. of Congo, and the Sudan. This paper attempts to investigate the aforementioned trade activities and its aftermath environmental concerns.